Revised typification of the Linnaean name Lobelia zeylanica (Campanulaceae) - Khan, Raees; Abidin, Sheikh Zain Ul; Ahmad, Mushtaq; Altinordu, Fahim (Phytotaxa, 2017)
A previously designated lectotype for the name Lobelia zeylanica is here superseded since the priority of type choice was violated, and a new lectotype is designated using a specimen collected by Osbeck and kept at the Swedish Museum of Natural History (S).